Perspectives of Quality by Design Approach in Nanomedicines Development - Beg, Sarwar; Akhter, Sohail; Rahman, Mahfoozur; Rahman, Ziyaur (Current Nanomedicine, 2017)
Background: Quality by Design (QbD) is a common word these days, where the concepts possess multidimensional applications in pharmaceutical product development. QbD as an approach has excellent prospective in nanomedicines scale-up. Method: Being instituted by ICH and USFDA, QbD primarily emphasizes on product and process understanding for producing finished products meeting the customer satisfaction. It works on the principle of envisioning product quality at very first stage for avoiding quality crisis. QbD has multiple advantages including development of high quality drug products and robust processes, reduces failures, and ultimately improves customer satisfaction for meeting the regulatory demands. As far as the USFDA is concerned, the agency is expecting implementation of QbD in the applications filed for approval of new drug products and generic products. Owing to the high degree of fruition and increasing demand of the concept, the application of QbD has percolated to almost all types of pharmaceutical formulations including the complex nanotechnology-based products and devices. The agency is an encouraging industry to focus more on adopting QbD-oriented development of nanomedicine for ease of monitoring their quality, safety and efficacy. Results: Looking into the current need and demand of the concept, the present article provides a holistic account on the fundamentals principles and vital elements of QbD, followed by special emphasis with respect to the development of nanotechnology products. Conclusion: Concisely, this present article is a help to the formulation and biomedical scientists working on the development of nanomedicines using the QbD principles.
Keywords: robustness